A Comparative Immunohistochemical Study of Anal Canal Epithelium in Humans and Swine, Focusing on the Anal Transitional Zone Epithelium and the Anal Glands. Issue 5 (20th December 2017) - Muranaka, Futoshi; Nakajima, Tomoyuki; Iwaya, Mai; Ishii, Keiko; Higuchi, Kayoko; Ogiwara, Naoko; Miyagawa, Shinichi; Ota, Hiroyoshi
ABSTRACT: To better understand the cellular origins and differentiation of anal canal epithelial neoplasms, the immunohistochemical profiles of the anal canal epithelium in humans and swine were evaluated. Formalin‐fixed tissue sections were immunostained for mucin (MUC: MUC2, MUC5AC, MUC5B), desmoglein 3 (DGS3), p63, CDX2, SOX2, and α‐smooth muscle actin (α‐SMA). The anal transitional zone (ATZ) epithelium covered the anal sinus and consisted of a stratified epithelium with mucous cells interspersed within the surface lining. Anal glands opened into the anal sinus. Ducts and acini of intraepithelial or periepithelial mucous type were the main structures of human anal glands, whereas those of swine were compound tubuloacinar mixed glands. Distal to the ATZ epithelium, non‐keratinized stratified squamous epithelium merged with the keratinized stratified squamous epithelium of the perianal skin. MUC5AC expression predominated over MUC5B expression in the ATZ epithelium, while MUC5B expression was higher in the anal glands. SOX2 was positive in the ATZ epithelium, anal glands, and squamous epithelium except in the perianal skin. In humans, DGS3 was expressed in the ATZ epithelium, anal gland ducts, and squamous epithelium. p63 was detected in the ATZ epithelium, anal glands, and squamous epithelium. Myoepithelial cells positive for α‐SMA and p63 were present in the anal glands of swine. Colorectal columnar cells were MUC5B + /MUC2 + /CDX2 + /MUC5AC − /SOX2 − . The ATZ epithelium seems to be a distinctive epithelium, with morphological and functional features allowing smooth defecation. The MUC5AC + /SOX2 + /MUC2 − /CDX2 − profile of the ATZ epithelium and anal glands is a useful feature for diagnosing adenocarcinoma arising from these regions. Anat Rec, 301:796–805, 2018. © 2017 Wiley Periodicals, Inc.